The Effect of Work Motivation and Self-Actualization on Work Productivity of Nurses at Iskandar Muda Hospital, Banda Aceh - Fachri, Muhammad (Dinasti Publisher, 2024)
The purpose of this study was to determine and analyze: (1) Motivation; Actualization; (3) Productivity; and (4) The Effect of Work Motivation and Self-Actualization on Work Productivity of Nurses in the Surgical Poly of Iskandar Muda Hospital Banda Aceh, both simultaneously and partially. The research method used in this research is descriptive survey and explanatory survey, the analysis used in this research is the Nurses in the Surgical Poly of Iskandar Muda Hospital Banda Aceh with a sample of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that the Productivity of Nurses in the Surgery Poly of Iskandar Muda Hospital Banda Aceh turned out that most of the Nurses gave very good responses; Work Productivity of Nurses in the Surgery Poly of Iskandar Muda Hospital Banda Aceh in general can be said to be good, Work Productivity of Nurses in the Surgery Poly of Iskandar Muda Hospital Aceh is currently considered good seen from the results of data processing and analysis results of 0.894. Work motivation and self-actualization simultaneously affect the work productivity of Nurses at the Iskandar Muda Hospital Surgery Poly in Banda Aceh. However, partially work motivation of 0.673 is more dominant in influencing the work productivity of nurses than self-actualization of 0.360. Thus Work Motivation is more dominant in influencing Work Productivity, being the first priority in improving Nurse performance. then the Iskandar Muda Banda Aceh Hospital Surgery Room is expected from the leadership to continue to be able to provide Work Motivation to nurses on a regular basis so that in providing services in the Surgical Poly runs optimally as well as nurses are included in training and education, so that they are able to work well and gain the trust of patients or the public.